2022
DOI: 10.3389/fmicb.2022.831455
|View full text |Cite
|
Sign up to set email alerts
|

Current Perspectives on Gastrointestinal Models to Assess Probiotic-Pathogen Interactions

Abstract: There are different models available that mimic the human intestinal epithelium and are thus available for studying probiotic and pathogen interactions in the gastrointestinal tract. Although, in vivo models make it possible to study the overall effects of a probiotic on a living subject, they cannot always be conducted and there is a general commitment to reduce the use of animal models. Hence, in vitro methods provide a more rapid tool for studying the interaction between probiotics and pathogens; as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 217 publications
0
10
0
Order By: Relevance
“…There are different models available that mimic the human intestinal epithelium and are thus available for studying probiotic and pathogen interactions in the gastrointestinal tract. Standard 2D models are comprised of culture plates as well as Transwell inserts, and newer 3D models like organoids, enteroids, and organ-on-achip have been built to assess probiotic-pathogen interactions [86]. Chen et al found that the inhibition of H. pylori adhesion and the invasion of gastric epithelial cells and interleukin-8 production were significantly decreased by treatment with the Lactobacillus strains by using an in vitro cellbased model [87].…”
Section: Cell and Organoid Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are different models available that mimic the human intestinal epithelium and are thus available for studying probiotic and pathogen interactions in the gastrointestinal tract. Standard 2D models are comprised of culture plates as well as Transwell inserts, and newer 3D models like organoids, enteroids, and organ-on-achip have been built to assess probiotic-pathogen interactions [86]. Chen et al found that the inhibition of H. pylori adhesion and the invasion of gastric epithelial cells and interleukin-8 production were significantly decreased by treatment with the Lactobacillus strains by using an in vitro cellbased model [87].…”
Section: Cell and Organoid Modelsmentioning
confidence: 99%
“…In addition, animal models provide the possibility to collect samples from different parts of the gastrointestinal tract that is not possible within clinical trials. Although mice and rats are most frequently used, Caenorhabditis elegans, honey bees, Ciona robusta, fruit flies, and greater wax moths also have been developed for assessing probiotic-pathogen interactions [86]. Chen et al indicated that colonization of H. pylori and induced stomach inflammation were alleviated by Lactobacillus strains [87].…”
Section: Cell and Organoid Modelsmentioning
confidence: 99%
“… 6 Additionally, intestinal microorganisms play an important role in intestine functions. 7 12 These processes are essential for maintaining intestinal homoeostasis. 13 16 …”
Section: Introductionmentioning
confidence: 99%
“…6 Additionally, intestinal microorganisms play an important role in intestine functions. [7][8][9][10][11][12] These processes are essential for maintaining intestinal homoeostasis. [13][14][15][16] Animal models, such as those of mice and pigs, are famous for studying intestinal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is ongoing controversy on the use of probiotics in terms of the consistency of clinical efficacy 20 and the reproducibility of experimental outcomes in various surrogate models 21 . Notably, it has been challenging to experimentally investigate the beneficial effect of probiotic bacteria on the leaky gut, where limited models to validate their preventive and therapeutic functions have remained to be resolved.…”
Section: Introductionmentioning
confidence: 99%